PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DENGAN MODEL INKUIRI TERBIMBING BERBASIS LITERASI SAINS PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA BAGI SISWA KELAS VIII SMP - Risma Widia; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop quality student worksheets in terms of the implementation of the syntax of guided inquiry models and indicators of scientific literacy in the material of the circulatory system in humans for VIII grade students of junior high school. This research was conducted in two places, namely for the validation of student worksheets by the validator and a limited trial phase I was conducted at the Biology Education Campus of the Teaching and Education Faculty (FKIP) of Riau University and a limited trial phase II of the student worksheets that had been developed was carried out at SMPN 4 Pekanbaru. When the research began in April-October 2019. This study used an Reasearch and Development (RnD) with the ADDIE’smodel and was carried out in 5stages, namely analysis, design, development, implementation and evaluation. In his research, we does by developments phase. Data collection instruments in the form of validation sheets and respondent sheets. The results of the LKPD validation with the guided inquiry model based on scientific literacy are at an average value of 3.51 with a very valid category. The results of a limited test score are 3.62 with a very good category. It can be conclude thatLKPD with a guided inquiry model based on science literacy is feasible to be implemented on a broader scale.KeyWords: Student’s worksheet, guided inquiry’s model, scientific’s literacy